Irradiation of materials with short, intense ion pulses at NDCX-II. (31st May 2017) - Seidl, P.A.; Barnard, J.J.; Feinberg, E.; Friedman, A.; Gilson, E.P.; Grote, D.P.; Ji, Q.; Kaganovich, I.D.; Ludewigt, B.; Persaud, A.; Sierra, C.; Silverman, M.; et al.
Abstract: We present an overview of the performance of the Neutralized Drift Compression Experiment-II (NDCX-II) accelerator at Berkeley Lab, and report on recent target experiments on beam-driven melting and transmission ion energy loss measurements with nanosecond and millimeter-scale ion beam pulses and thin tin foils. Bunches with around 10 11 ions, 1 mm radius, and 2–30 ns full width at half maximum duration have been created with corresponding fluences in the range of 0.1–0.7 J/cm 2 . To achieve these short pulse durations and mm-scale focal spot radii, the 1.1 MeV [megaelectronvolt (10 6 eV)] He + ion beam is neutralized in a drift compression section, which removes the space charge defocusing effect during final compression and focusing. The beam space charge and drift compression techniques resemble necessary beam conditions and manipulations in heavy ion inertial fusion accelerators. Quantitative comparison of detailed particle-in-cell simulations with the experiment plays an important role in optimizing accelerator performance.